Türkiye'deki Diş Hekimlerinin Antibiyotik ve Profilaksi Bilgilerinin Değerlendirilmesi - Ercan Durmuş; Hasan Küçükkolbaşı; Ahmet Aktı; Rabia Gür; Gökhan Gürses (Selcuk University Press, 2023)
Introduction: Inappropriately prescribed antibiotics accelerate the formation of antibiotic-resistant bacteria. This circumstance creates a problematic situation in terms of public health. This study aims to measure dentists' antibiotic/prophylaxis knowledge and awareness of antibiotic resistance in Turkey based on two case scenarios. Materials Methods: Dentists in Turkey are invited by open invitation posts on various social media applications for our twelve-question online survey. The scoring was shaped based on answers to measure antibiotic/prophylaxis knowledge. The collected data were statistically analyzed by SPSS Statistics 22. Results: 321 participants answered all questions included in the study. The statistical analyses showed a significant difference in the evaluations according to gender, title, graduation time, and workplace. Conclusion: Inappropriate antibiotic prescription by dentists is common in Turkey. Dentists should receive more undergraduate lessons, and taking reminder antibiotic courses at regular intervals after graduation can contribute to keeping their knowledge up to date.